A Rare Case of Paired Congenital Cervical Aneurysms in a Communicating Vein: Clinical and Imaging Findings in a Pediatric Patient - Grigol Keshelava; Zurab Robakidze; Igor Mikadze (Pathophysiology, 2025)
A four-year-old female patient was admitted for evaluation after a mass on the right side of her neck was noticed during straining (Valsalva maneuver). The family first observed the mass when the patient was one year old, and noted that it gradually increased in size over time. A family history assessment revealed no known genetic disorders. The patient underwent neck ultrasonography and computed tomography angiography (CTA), which revealed two aneurysms in a right-sided communicating vein. One aneurysm was located above the jugular notch, and the other was located in the retro-parotid region. The presence of two venous aneurysms in a right-sided communicating vein—one above the jugular notch and the other in the retro-parotid region—suggests a rare and apparently benign congenital anomaly. The progressive enlargement of these malformations warrants close monitoring and surgical intervention, and long-term follow-up may be necessary to prevent complications such as thrombosis, rupture, or compression of adjacent structures.